Phytochemical Investigations and Nutritive Potential of Eight Selected Plants from Ghana - Rita A. Dickson; Kofi Annan; Theophilus C. Fleischer; Isaac K. Amponsah; Kwabena Nsiah; J.A. Oteng (Journal of Pharmacy and Nutrition Sciences, 2012)
In Ghana and most parts of Africa, traditional vegetables and herbs are important sources of proteins, minerals and vitamins for the general population. In order to meet the daily recommended nutritional requirements for the betterment of health and general well being, these vegetables and herbs are seen as an integral part of the diet of the people. In this study, the phytochemical constituents, mineral content and nutritive potential of eight selected plants, Amaranthus incurvatus (Amaranthaceae), Launaea taraxacifolia (Asteraceae), Manihot utilissima (Euphorbiaceae), Ceiba pentandra (Malvaceae), Manniophyton fulvum (Euphorbiaceae), Corchorus olitorius (Malvaceae), Talinum triangulare (Portulacaceae) and Hibiscus sabdariffa (Malvaceae), were evaluated using standard methods. The results showed that, alkaloids, glycosides, flavonoids, terpenoids, phytosterols and tannins are present in almost all the plant samples. Vitamin C is the abundant vitamin present in the selected plants followed by vitamin A. The crude protein ranged from 7.44 – 31.5% with A. incurvatus and T. triangulare providing the highest amount. The elemental analysis in mg/100g of dry matter revealed H. sabdariffa calyx contained the highest amount of magnesium (Mg) and iron (Fe), providing about 43.48% and 72% of the respective daily value of these minerals. The sodium (Na) and potassium (K) contents of the samples were within recommended daily values except H. sabdariffa which exceeded it daily value for potassium (K). The selected plants may therefore be considered asviable and cheap sources of dietary nutrients and their incorporation in diets may be said to be scientifically justifiable.